1993
DOI: 10.1016/s0022-5347(17)36032-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Immunoreactivity of Epidermal Growth Factor Receptor in Benign, Dysplastic and Malignant Prostatic Tissues

Abstract: To investigate epidermal growth factor receptor (EGFr) presence in the prostate, monoclonal antibody (clone EGFR1) immunohistochemical examination of radical prostatectomy specimens was performed (n = 37). All prostatic specimens contained benign prostatic hyperplasia (BPH) and/or dysplasia (prostatic intraepithelial neoplasia or PIN), as well as prostatic carcinoma (CaP). Areas of dysplasia were further categorized as to the basal cell layer and the luminal cell area. BPH, PIN, and CaP tissues in each specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 12 publications
2
32
0
1
Order By: Relevance
“…EGFR expression has also been correlated with higher histological grade, increased S-phase fraction and poorer prognosis of prostate cancers (Visacorpi et al, 1992). However, other immunohistochemical investigations have shown greater EGFR expression in normal and hyperplastic prostate compared with prostate cancer (Maygarden et al, 1992;Mellon et al, 1992;Ibrahim et al, 1993). Our study demonstrated a higher level of EGFR expression in the androgen-independent PC3 and DU145 cell lines than in LNCaP cells or in normal epithelial cells.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…EGFR expression has also been correlated with higher histological grade, increased S-phase fraction and poorer prognosis of prostate cancers (Visacorpi et al, 1992). However, other immunohistochemical investigations have shown greater EGFR expression in normal and hyperplastic prostate compared with prostate cancer (Maygarden et al, 1992;Mellon et al, 1992;Ibrahim et al, 1993). Our study demonstrated a higher level of EGFR expression in the androgen-independent PC3 and DU145 cell lines than in LNCaP cells or in normal epithelial cells.…”
Section: Discussionsupporting
confidence: 45%
“…The EGFR and its ligands, EGF and TGF-a, have been identified in benign and malignant prostatic tissues and cells (Wilding et al, 1989; Connolly and Rose, 1991;Hofer et al, 1991;Fong et al, 1992;Maygarden et al, 1992;Ching et al, 1993;Ibrahim et al, 1993). The functional role of the TGF-a-EGFR interaction has been demonstrated in cultured prostate cancer cells (Hofer et al, 1991;Fong et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,13,41,42 Data on the relationship between Gleason score and EGFR expression are also conflicting. [43][44][45] In recent papers, there is more agreement in the association between EGFR immunostaining and advanced adenocarcinoma stage, high Gleason score and preoperative PSA. These results support a role for EGFR expression in the development of prostate cancer and in the progression to an androgen-independent, hormone-refractory clinical phase.…”
Section: Discussionmentioning
confidence: 99%
“…c-Cbl belongs to a family of E3 ubiquitin ligases (Swaminathan and Tsygankov, 2006). It binds to and ubiquitinates a range of receptor tyrosine kinases including EGFR (de Melker et al, 2001) and MET (hepatocyte growth factor receptor) (Peschard et al, 2001), both of which are localised to the basal layer and have reported roles in prostate proliferation and differentiation (Ibrahim et al, 1993;Pisters et al, 1995;Knudsen and 2004; Schlomm et al, 2007). Receptor tyrosine kinases bound to c-Cbl are targeted to the endosomal compartment from where they are either trafficked to lysosomes for degradation or recycled back to the plasma membrane (Thien and Langdon, 2001).…”
Section: Discussionmentioning
confidence: 99%